A magnetic loop antenna for partial discharge measurements on GIS. (February 2020) - Rodrigo Mor, A.; Castro Heredia, L.C.; Muñoz, F.A.
Highlights: PD signals can be detected by pick-up coils installed in the GIS compartments. Magnetic detection of PD signals can achieve high sensitivity. Calibration to pC is feasible in GIS although strongly dependent on the signal amplitude. Abstract: This paper presents a magnetic loop antenna for partial discharge (PD) measurements on gas insulated systems (GIS). The antenna is based on a single shielded loop inserted in the dielectric window of a GIS that measures the PD currents propagating in TEM mode. The paper describes the relevant parameters of the antenna and the antenna performance in combination with a transimpedance amplifier. A calibration method for charge estimation is presented along with laboratory experiments with free moving particle, surface and corona discharges in SF6 test cells. The results show the suitability of the magnetic antenna for PD detection and the charge evaluation performance. Under laboratory conditions, the antenna sensitivity is in the order of 1 pC at a few meters from the PD source.